Metodologías de enseñanza y uso de las TIC en el proceso de formación académica de las carreras Online del Instituto Superior Tecnológico Sudamericano - Quevedo Jumbo, Jackson Michael (2023)
The research was developed under the premise of knowing and identifying the alternatives in the teaching process. Thus, the analysis of learning methodologies and the relationship of ICT used by the teacher in the academic training process was proposed, focused on students of the online modality of the Instituto Superior Sudamericano in the city of Loja. Meanwhile, the research is quantitative and correlational in nature because its purpose was to measure the variables and their relationship in the investigative process. In this sense, analytical - synthetic research methods and inductive - deductive method were used, which facilitated the development of research from a pedagogical and didactic point of view. In addition, with the help of the research instrument (survey) it was identified that the methodologies used mostly by the teachers at the South American Higher Technological Institute are; collaborative learning, project-based learning, problem-based learning, case methodology and gamification. On the other hand, digital resources are frequently, videoconference platforms, office tools, chat interaction, collaborative work tools and virtual forums. In this way, the academic training process is oriented to the teaching method that meets the needs of the student with the frequent use of ICT. Finally, the investigative process determined that there is a direct relationship between learning methodologies and the use of ICT, because it facilitates the construction of knowledge. That is, its importance is closely related to technological advances and the need to guarantee quality in the teaching process.